2022
DOI: 10.21608/jssae.2022.128096.1068
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Salt-Tolerant Plant Growth Promoting Bacteria In Increasing The Resistance of Canola to Salt-Stress

Abstract: Salinity, a major environmental stress that inhibits agricultural productivity, has a negative impact on plant growth and development. The goal of this study was to use salt-tolerant bacteria to improve the plant's ability to resist salt-stress and to achieve high canola productivity in saline soil conditions. The rhizobacteria strains, Acinetobacter radioresistens (NBRC 102413) and Enterobacter cloacae (NBRC 102413) were evaluated for their ability to produce organic acids and phytohormones (IAA). A field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Saline soils are also a challenge for cereal crop production and PGPB use was able to both promote the growth of cereals and remediate soils [59,81,169,171]. The bacteria were selected for their salt-resistant characteristics and used in field experiments with canola, where many yield components were enhanced by the PGPB inoculation [80]. Other recent experiments in saline conditions include work with rice [133,137] and maize [90].…”
Section: Recent Research In Pgpb and Agricultural Food Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saline soils are also a challenge for cereal crop production and PGPB use was able to both promote the growth of cereals and remediate soils [59,81,169,171]. The bacteria were selected for their salt-resistant characteristics and used in field experiments with canola, where many yield components were enhanced by the PGPB inoculation [80]. Other recent experiments in saline conditions include work with rice [133,137] and maize [90].…”
Section: Recent Research In Pgpb and Agricultural Food Cropsmentioning
confidence: 99%
“…The majority of recent studies have shown overall benefits for plant and grain yield, but other yield components are also of interest. For example, oil yield increases in canola [71,80] and soybean [152,155] are important outcomes of PGPB crop inoculation. Other studies have looked at the yield of human nutritional components, such as the amplified bioavailability of iron in rice [131,139] and the enhancement of nutrients in beans [67], apples [57], and wheat [166].…”
Section: Recent Research In Pgpb and Agricultural Food Cropsmentioning
confidence: 99%